Technology and skills in Malaysia - Anuwar Ali; Osman Rani, Hassan; Toh , Kin Woon (Institute of Southeast Asia Studies, 1986)
Industrialization in Malaysia - Transfer, adaptation, and development of technology - Transfer, adaptation, and development of technology : case studies - Summary and policy implications.